Active commuting to school, positive health and stress in Spanish children. - Chillón, P.; Villén-Contreras, R.; Pulido-Martos, M.; Ruiz, J. R. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
Promotion of daily physical activity in young people such as active commuting to school (use of active means of transportation such as walking or cycling), may have important benefits for the health. The aim was to analyze the association of active commuting to school with positive health and stress related-variables in Spanish children. A total of 366 children (172 females) from 4 schools (aged 7-11 years old, 9,3±0,8 años) participated. Commuting mode to school was assessed through a weekly questionnaire: Mode and frequency of commuting to and from school. Subjective happiness, subjective well-being cognitive type and affective type, dispositional optimism and stress were assessed with the Subjective Happiness Scale, Satisfaction with Life Scale and Positive and Negative Affect Schedule, respectively. Active commuting to school was inversely associated with stress (ß=-0.235±0.079, p=,004) after adjustment for sex, age and educational level of the mother. Children who actively commuted more times weekly to school have lower stress levels. Initiatives promoting active commuting to school are required, because it has positive effects on the physical and emotional health, and it might be a way to control effectively the stress levels among Spanish children.